EP562 Incidence of isolated tumor cells after sentinel lymph node ultrastaging in early stage endometrial cancer. (1st November 2019) - Locati, V; Corvetto, E; Fais, M; Russo, M; Proto, A; Candotti, G; Angioni, S; Fanni, D; Mais, V; Peiretti, M
Abstract : Introduction/Background: To describe the accuracy and detection rate of sentinel lymph node (SLN) identified by dual cervical indocyanine green (ICG) injection, underlining the incidence of Isolated Tumor Cells (ITC) following SLN ultrastaging. Methodology: Between December 2015 and May 2019, 40 women with early stage Endometrial Cancer (EC) were scheduled for total laparoscopic or laparotomic hysterectomy, bilateral oophorectomy and SLN detection. Results: A total of 40 procedures was performed. The patient mean age was 65 years (SD 12.2) and mean body mass index was 26 kg/m 2 (SD 6.9). Histological types were endometrioid adenocarcinoma in 29 cases (73%), 7 endometrial hyperplasia (19%), 3 serous adenocarcinoma (5%), 1 mixed histology (3%). The detection rates were as follow: 97% (39/40) overall for SLNs; unilateral and bilateral mapping of SLNs were achieved in 20% and 72% of subjects respectively (undetermined laterality in 2 cases and unobserved SLN in 1 case). The main lymphatic stations were external iliac (57%) and interiliac (45%). Positive SLNs were 8, identified in 7 out of 40 patients (17%), including 4 patients with ITC (57% - 4/7) (2 in the EI area, 1 in the II area, 1 in the interiliac area). The oncological risk of ITC positive patients was in 1 low, 2 intermediate and 1 high/intermediate risk cases. All patients with ITC were discussed by a multidisciplinary team and none of them received adjuvant therapy. Five months after surgery, 1 patient presented inguinal node and vaginal cuff relapse. She underwent EBRT& BRT with a complete response. At this moment all these patients are free of disease. Conclusion: SLN ultrastaging increases the number of nodes considered positive, especially the identification of ITC. In our population the overall incidence of ITC was 10% and in those who had positive SLN, ITC were detected in 57%. We observed in these patients an excellent prognosis. Disclosure: Nothing to disclose.